2010
DOI: 10.1007/s13225-010-0030-8
|View full text |Cite
|
Sign up to set email alerts
|

Trichocybe, a new genus for Clitocybe puberula (Agaricomycetes, Agaricales)

Abstract: Trichocybe, a new genus of Agaricales, is described to accommodate the rare species Clitocybe puberula characterized by an isolated phylogenetic position. Trichocybe is distinguished from its allied clitocyboid genera by a unique combination of macro-and micromorphological characters, including a Gymnopus-like habitus, a pubescent pileus with squamulose flocci, an eccentric stipe growing on wood debris, a putrescent non-reviviscent context, a strongly farinaceous odour, rare but clearlydifferentiated cheilocys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Nucleotide sequences of LSU obtained from this study (Table 1) were aligned with the sequences of the database in Vizzini et al (2010) to determine the taxa position (see supplementary material, Table 2). Sequences were also selected according to the outcomes of other phylogenetic studies of Agaricales (Table 2, Moncalvo et al, 2002;Matheny et al, 2006).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleotide sequences of LSU obtained from this study (Table 1) were aligned with the sequences of the database in Vizzini et al (2010) to determine the taxa position (see supplementary material, Table 2). Sequences were also selected according to the outcomes of other phylogenetic studies of Agaricales (Table 2, Moncalvo et al, 2002;Matheny et al, 2006).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Bayesian analysis was conducted using MrBayes v.3.1.2 (Ronquist and Huelsenbeck, 2003). Bayesian analyses were run for 10 000 000 generations for the LSU dataset with the same parameters of Vizzini et al (2010). The topologies were used to generate a 50% majority rule consensus tree.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…Genera with higher numbers of taxa are Mycena (Pers.) Roussel (56) Mycol Prog, and Gymnopus inexpectatus Consiglio, Vizzini, Antonín & Contu (Vizzini et al 2008 Vizzini, A, Consiglio, G, Antonin, V and (Vizzini et al 2010), and Tricholomopsis flammula Métrod.…”
Section: Introductionmentioning
confidence: 99%
“…Recent molecular studies that included a significant number of Clitocybe species , Matheny et al 2006, Vizzini et al 2010a,b, 2011 have shown that taxa in this traditional genus do not form a monophyletic group but rather a heterogeneous artificial set of disparate and (in many cases) phylogenetically unrelated taxa (the so-called clitocyboid fungi or Clitocybe s.l. ).…”
Section: Introductionmentioning
confidence: 99%